Resilience to evolving drinking water contamination risks: a human error prevention perspective - Tang, Yanhong; Wu, Shaomin; Pollard, Simon J. T.; Hrudey, Steve E. (Elsevier, 2013)
Human error contributes to one of the major causes of the prevalence of drinking water contamination incidents. It has, however, attracted insufficient attention in the cleaner production management community. This paper analyzes human error appearing in each stage of the gestation of 40 drinking water incidents and their causes, proposes resilience-based mechanisms and tools within three groups: consumers, drinking water companies, and policy regulators. The mechanism analysis involves concepts and ideas from behavioral science, organizational culture, and incentive analysis. Determinants for realizing cleaner drinking water system are identified. Future efforts and direction for embedding resilience into drinking water risk management are suggested. This paper contributes to identifying a framework and determinants of resilience-oriented management mechanisms for cleaner drinking water supply, and, is essential for ensuring the successful practice of managing drinking water contamination risks. It harmonizes the two fields of risk management and resilience thinking, and provides a new insight for implementing effective actions in drinking water-related sectors.
Keywords: Drinking water incident; Contamination; Human error; Resilience; Risk management